Development of Breathing Cartoon-Based Learning Media to Enhance Students' Higher-Order Thinking Skills at Madrasah Ibtidaiyah 21 Aceh Besar - Daniah, Daniah; Hayati, Zikra; Trina Sari, Novi; Hafiz, M (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Metro, 2025)
This study explores the development and effectiveness of breathing cartoon-based instructional media to address the lack of suitable teaching materials for the human respiratory system at Madrasah Ibtidaiyah Negeri 21 Aceh Besar. Teachers primarily utilize lower-order thinking skills questions, which may limit students' ability to develop higher-order thinking skills . The study employed a research and development approach to bridge this gap, following the Borg and Gall model to design, validate, and assess the instructional media. Expert validation results indicated a 97% feasibility score, classifying the media as highly suitable for classroom implementation. Teacher responses yielded an 84.6% engagement rate, while student responses reached 95.33%, both categorized as highly engaging. Pretest and posttest data from fifth-grade students demonstrated that 12 students scored above 90, achieving a high N-gain (g > 0.7), while five students obtained a moderate N-gain (0.3 < g < 0.7). The average N-gain score of 0.81 (81.41%) confirmed the media’s high effectiveness. These findings suggest that breathing cartoon-based instructional media is pedagogically feasible and highly effective in enhancing students’ high order thinking skills, reinforcing the need for interactive and innovative learning tools in science education. Keywords: higher-order thinking skills, breathing cartoon